PENGEMBANGAN APLIKASI "CERITA WAYANG DETIK-DETIK PROKLAMASI” BERBASIS GAWAI UNTUK SISWA SEKOLAH DASAR - Rosid, Dian Perdana Sulistya; Desstya, Anatri; Sumardjoko, Bambang (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This research aims to develop a mobile-based application titled "Cerita Wayang Detik-detik Proklamasi" (Puppet Story of the Moments of Proclamation) for elementary school students on the material of Indonesia's Proclamation of Independence, assessed in terms of its validity and specifications. This research is a development study (R&D) using the 4D model (define, design, develop, disseminate), limited to the development stage. The subjects involved in this study include 6 teachers (from grades 1–6) and 14 fifth-grade students from SDN Bakulan, Cepogo, Boyolali, as well as material experts, media experts, and teachers who are learning practitioners as validators to assess the suitability and validity of the developed media. Data collection techniques were carried out through observation, documentation, interviews, and product validation questionnaires. The data analysis technique in the define stage used qualitative data analysis, and in the develop stage, descriptive analysis was employed to evaluate the validity of the application based on the trial results and feedback from validators and users. The results of this development study produced a product in the form of the "Cerita Wayang Detik-detik Proklamasi" application, which has very high validity from material experts, media experts, and practitioners, with an average score of 95. The developed learning application was also assessed through various feasibility tests, both in small groups and large groups, and received a score of 94.5, categorized as "Very High" in terms of text readability, clarity of the learning flow, suitability of images and animations with the material, and the ability to facilitate learning. The researcher hopes that the results of this study can be applied on a larger scale and contribute as a practical solution to teach the Proclamation material effectively and enjoyably through the use of technology.